Cholangiocarcinoma in South India: unprecedented, unanticipated and underreported - Nair, Priya; B., Harshavardhan Rao; Koshy, Anoop K.; Sudhindran, Surendran; Pavithran, K.; Venu, Rama P. (International Journal Of Community Medicine And Public Health, 2021)
Background: The incidence of CCA in India is on the rise especially in Kerala. However, the clinical profile and outcome of these patients has never been reported. The aim of this study was to identify region specific epidemiological trends and natural history of CCA in Kerala. Methods: This was a single centre, hospital based epidemiology study where incident cases of CCA from January 2014 to August 2016 were studied. Patient demographics and relevant clinical and laboratory data, imaging studies and treatment, were recorded in a predesigned Performa. Results: A total of 137 patients (mean age 62.92 ± 12.5 years, M:F=1.2) were studied of which 109 patients had Hilar CCA (pCCA), 16 patients had Distal CCA (dCCA) and 12 patients had Intrahepatic CCA (iCCA). A majority of patients were from coastal areas and rubber plantations. Known risk factors were absent in our patients. Bismuth Type IV disease was seen in 55 patients (50.5%). Most intrahepatic CCA (iCCA) (7/12) patients had stage IV disease at presentation. Curative resection was possible in 17/38 patients (44.7%). Patients who underwent treatment with a curative intent were younger with less advanced disease and therefore, had a significant 3 month, 6 month and 1 year survival advantage (p<0.05). The overall 1-year mortality was 66.1% (91/137). The 30-day post-op mortality was 4.3%. Conclusions: This study highlights a unique epidemiological pattern in our patients characterised by absence of known risk factors and unique geographic clusters. Palliative chemotherapy showed a significant survival benefit in this study which needs further validation.